2011
DOI: 10.1111/j.1467-8608.2011.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumer orientation toward returns: unethical dimensions

Abstract: As customer return rates increase, retailer bottom lines suffer from customers' misuse of the policies and to the ethics of such practice. The purpose of this study is to explore customers' orientation toward return behaviors, and to develop a return orientation assessing these dimensions. This research identified three dimensions relevant to consumer return behavior: the planned/unethical returner; the eager returner; and the reluctant/educated returner. A retest with another sample confirmed these three dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…The result of the study showed that selling pressure and ethical sales climate are found to have a positive significant relationship to ethical behaviors. As pointed out by [20,52,53], selling pressure is focused on retaining the relationship with the customers and this encompasses a range of activities inherent of the company's objective and agents' concerns for customers' need. Thus, in service industry like Takaful putting customers' interest should be priority [54], and agents tend to sell product that are beneficial to the customers [55].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The result of the study showed that selling pressure and ethical sales climate are found to have a positive significant relationship to ethical behaviors. As pointed out by [20,52,53], selling pressure is focused on retaining the relationship with the customers and this encompasses a range of activities inherent of the company's objective and agents' concerns for customers' need. Thus, in service industry like Takaful putting customers' interest should be priority [54], and agents tend to sell product that are beneficial to the customers [55].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Similarly, Wachter et al (2012) identified three dimensions that are relevant for consumer return behaviour: the planned or unethical returner (customers who intentionally plan unethical returns), the eager returner (customers who see returning as a good decision and feel good when they complete a return) and the reluctant or educated returner (customers who find returning embarrassing or feel guilty about it). Previous studies have also identified demographics (e.g.…”
Section: Returning Behaviourmentioning
confidence: 99%
“…Consequently, while some consumers may have justified reasons for returning items they have bought or ordered, other consumers may take advantage of a free return policy (see Wachter et al 2012). This phenomenon is labelled as 'fraudulent returning', and can be defined as 'the returning of a product broken by the customer after purchase or the returning of a non-faulty product after it had been used' (Harris 2010, 734).…”
Section: Returning Behaviourmentioning
confidence: 99%
See 2 more Smart Citations